Coherent quantum scattering of CH4 from Ni(111). Issue 32 (1st August 2017) - Al Taleb, Amjad; Farías, Daniel
Abstract : We have measured high-resolution angular distributions of methane scattered from a Ni(111) surface at incident energies between 68.9 meV and 108.6 meV. Abstract : We have measured high-resolution angular distributions of methane scattered from a Ni(111) surface at incident energies between 68.9 meV and 108.6 meV. A sharp and intense specular peak has been observed, in addition to sharp features corresponding to rotationally inelastic diffraction (RID) peaks along the two main symmetry directions of Ni(111). The intensity of the most intense RID peaks is ca. 50% of the specular one. The observation of sharp, coherent elastic peaks at such low incident energies suggests that single scattering dominates over trapping at these energies, and that the depth of the van der Waals well should be lower than 60 meV. In contrast, a broad angular distribution shifted from the specular position is observed from a graphene-covered Ni(111) surface under identical incident conditions. These results open up the possibility of studying the physisorption well between CH4 and a transition metal surface using high-resolution molecular beams.